1997
DOI: 10.1111/j.1939-1676.1997.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and Interindividual Variation in Urine Osmolality and Urine Specific Gravity in Healthy Pet Dogs of Various Ages

Abstract: Urine specific gravity (Usg) and urine osmolality (Uosm) are used routinely t o assess renal concentrating ability, but limited data on these variables are available for healthy dogs. Consequently, we studied the intra-and interindividual variations in Usg and Uosm in healthy dogs as well as the influence of age and gender on these variables. Dogs were selected for health and anestrus in female dogs through the use of a detailed questionnaire. Eighty-nine owners collected morning and evening urine samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
8
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 32 publications
(5 reference statements)
5
46
8
5
Order By: Relevance
“…Urinary cortisol-to-creatinine ratios reported here are higher than those reported by Beerda et al (2000) in four groups of dogs living in varying kennel conditions for longer than a year, and they are higher than the mean ratio reported by van Vonderen, Kooistra, and Rijnberk (1997) in companion dogs. The assumption that shelter dogs are more stressed than dogs residing in homes is thus supported by our findings.…”
Section: Discussioncontrasting
confidence: 82%
“…Urinary cortisol-to-creatinine ratios reported here are higher than those reported by Beerda et al (2000) in four groups of dogs living in varying kennel conditions for longer than a year, and they are higher than the mean ratio reported by van Vonderen, Kooistra, and Rijnberk (1997) in companion dogs. The assumption that shelter dogs are more stressed than dogs residing in homes is thus supported by our findings.…”
Section: Discussioncontrasting
confidence: 82%
“…doi:10. 1016/j.jtherbio.2004.09.003 in physiological functions have revealed that the two variabilities are often different (Gidal et al, 2000;Refinetti, 1989;Refinetti and Horvath, 1989;Symanski et al, 2001;van Vonderen et al, 1997). This difference in variabilities has important implications for clinical practice, whether in veterinary or human medicine.…”
Section: Introductionmentioning
confidence: 96%
“…6 Normal urine osmolality can range between 161 and 2830 mOsm in dogs. 10 The urine osmolality will increase when water intake is withheld as long as kidney function is normal. Each individual laboratory should establish the normal reference range in each species for its osmometer.…”
Section: Measuring Plasma Osmolalitymentioning
confidence: 99%
“…The normal values reported for plasma COP range from 14 to 27 mm Hg in the dog and 21 to 34 mm Hg in the cat. [10][11][12][13] Whole blood COP is reported to be 19.95 ± 2.1 mm Hg in the dog, and 24.7 ± 3.7 mm Hg in the cat. 14 When whole blood is being measured, the sample should be collected with lyophilized heparin.…”
Section: Measuring Colloid Osmotic Pressurementioning
confidence: 99%